Studi Kasus Strategi Adaptasi Sosial Mahasiswa Dengan Gangguan Bipolar - Moniqoe Emmanuel Briga Regita (Universitas Maritim AMNI Semarang, 2024)
Bipolar disorder affects a person’s affect and activities over a certain period of time. In manic and hypomanic episodes, a person with bipolar disorder experiences increased activity and affect in the form of increased energy and activity. In a depressive episode there is a decrease in affect, activity, and reduced energy. This study aimed to determine social adaptation of subjects with bipolar disorder in manic/hypomanic and depressive episode, describe impact of bipolar disorder on social environment of subjects with bipolar disorder, how subjects with bipolar disorder building good friendships, how subjects with bipolar disorder maintain social relationships when in depressive episode, and ability to socialize in campus setting. Researchers used qualitative methods with a case study approach. Data collection techniques use interviews and documentation. The analysis technique uses the help of QDA Miner software version 6.0.11. The results of this research show that a person with bipolar disorder have social adaptation strategies including providing understanding to others, self-control, moral adjustment, and respect for other.